(untitled) (Experimental biology, 2023)
This article presents an assessment of the state of green spaces in Aksu city, located in Pavlodar region in the north-east of the Republic of Kazakhstan. The analysis of the results is based on reliable data obtained as a result of a tree inventory conducted in 2022. The current state of tree and shrub plantations of the city was analysed, their species and age composition was established, with the determination of the number, category, type and vital state of plantations, the forecast in the short-term and long-term perspective of changes was made. The degree of greening to the demographic capacity of Aksu city was assessed. A high level of oxygen productivity of the territory was noted. The indicator of landscaping was 13.5 km2 of public green spaces per one resident of Aksu city.